Remote Training of SRL Users and Staff in a Global Pandemic. Issue 1 (18th November 2020) - Daniels, Kathleen; Conway, Alexis; Gardner, Rui; Martinez, Lola; Price, Kylie M.; Schneider, Sarah; Sheridan, Rachael; Srivastava, Jane; Thornton, Sherry
Abstract: The impact of the COVID‐19 pandemic on training and Shared Resource Laboratory (SRL) operations such as staffing, facility access, and social distancing, has affected facilities around the globe to different degrees based on restrictions set by various geographical and institutional settings. With these restrictions come unique challenges regarding user and staff training and education, for both theory and practice. Most notably, limitations in facility access, occupancy, staffing availability, network restrictions and trainee engagement call for innovative solutions for training when traditional in‐person options are not feasible. Through the use of remote access tools and prerecorded educational and training materials, SRLs are able to overcome these obstacles. Here, we focus on readily available technologies and general guidelines that SRLs in different environments can use for remote cytometry training and education, while highlighting key obstacles that still remain. Although SRLs may face initial struggles in transitioning trainings to a virtual format, remote technologies provide unique opportunities to advance current training programs. © 2020 International Society for Advancement of Cytometry